RADIATION GRAFTING OF STYRENE ONTO PTFE FILM - Yohan Yohan; Rifaid M. Nur; Lilik Hendrajaya; E. S. Siradj (Universitas Gadjah Mada, 2006)
Radiation grafting of styrene monomer onto poly(tetrafluoroethylene) (PTFE) film has been investigated. This research is emphasized on the conditioning of PTFE film. It was irradiated by γ-ray radiation at various irradiation dose from 2.5 - 12.5 kGy with dose rate 1.9 kGy/hour. Irradiated copolymer was then grafted by styrene monomer under various conditions. The results showed that degree of grafting increased by increasing irradiation dose, solvent concentration, temperature and time of grafting. The optimum condition of radiation grafting relatively was obtained at irradiation dose of 10 kGy, 2-propanol solvent, styrene concentration of 40 volume%, temperature and time of grafting of 70 oC and 6 hours each.